Medicine of the Future: Opportunities for Breakthrough through the Prism of Technology Foresight - Ilya Kaminskiy; Ludmila Ogorodova; Maxim Patrushev; Alexander Chulok (Foresight and STI Governance)
Many countries consider healthcare a priority area of development. Its future milestones lie in two key dimensions: social — combating common and complex diseases, and economic — establishing S&T basis that will provide leadership, or at least a decent niche in the global markets.